A Quantitative Description of the σ‐Donor and π‐Acceptor Properties of Substituted Phenanthrolines. Issue 23 (20th July 2016) - Ardizzoia, G. Attilio; Bea, Michela; Brenna, Stefano; Therrien, Bruno
Abstract : The bond between molybdenum and substituted 1, 10‐phenanthroline ligands in a series of [Mo(CO)4 (phen*)] complexes has been studied by combining experimental data ( ν CO ) with DFT calculations. First, natural orbitals for chemical valence (NOCV) were calculated: The resulting charge‐transfer magnitudes (Δ qi ) associated with the deformation density channels (Δ ϱi ) were related to σ‐donation and π‐back‐donation. Then, energy decomposition analysis was performed by applying the extended transition state (ETS) scheme. The outcomes of the ETS‐NOCV approach has allowed us to quantify the energetic contribution of both ligand‐to‐metal ( E σ ) and metal‐to‐ligand ( E π ) interactions. A new parameter ( T phen ) has been introduced comprising both E σ and E π and thus providing a descriptor for the overall electronic contribution given by phenanthrolines to the metal–ligand bond. This was corroborated by the linear correlation found between T phen and the ν CO vibration modes of [Mo(CO)4 (phen*)] complexes, at least for those containing a 2, 9‐unsubstituted phenanthroline. The case of [Mo(CO)4 (phen*)] derivatives with a 2, 9‐substituted phen* is also discussed. Abstract : Like players of opponent teams in rugby, σ and π contributions are involved in a sort of "electronic scrum" that determines the nature of metal–ligand bonds. An ETS‐NOCV study allowed us to quantify these contributions, associated with E σ and E π, in [Mo(CO)4 (phen*)] compounds. A new electronic parameter ( T phen ) comprising both E σ and E π has been introduced and correlated with experimental data.